Factors that Influence Organizational Performance in Manufacturing Companies in Batam City - Asri, Dhita Hafizha; Amanda, Xena (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2025)
This study aims to analyze the factors affecting Organizational Performance in manufacturing companies in Batam City, focusing on the mediating roles of Organizational Culture, Motivation, Strategic Planning, Challenges, and Program Performance. The research addresses performance issues frequently encountered in industrial sectors, particularly within competitive manufacturing environments. A total of 359 respondents, consisting of employees from a manufacturing company in Batam, were selected using the sampling technique proposed by Hair et al. Data analysis was conducted using SmartPLS to evaluate relationships between variables. The results indicate that Motivation significantly influences Organizational Performance, although the high path coefficient is accompanied by relatively small p-values. Strategic Planning also contributes positively to performance but with a lower effect. Conversely, Challenges were found to have a strongly negative impact on Organizational Performance, highlighting the critical need for effective management of organizational obstacles. These findings suggest that enhancing motivation and strategic planning, while proactively addressing challenges, can improve overall organizational outcomes. The study contributes valuable insights for company leaders and policymakers seeking to optimize performance in dynamic manufacturing settings.